2003
DOI: 10.1021/bi0341410
|View full text |Cite
|
Sign up to set email alerts
|

The Amyloid β Peptide (Aβ1-40) Is Thermodynamically Soluble at Physiological Concentrations

Abstract: Precipitation of the 39-43-residue amyloid beta peptide (Abeta) is a crucial factor in Alzheimer's disease (AD). In normal as well as in AD-afflicted brain, the Abeta concentration is estimated to be a few nanomolar. Here we show that Abeta(1-40) precipitates in vitro only if the dissolved concentration is >14 microM. Using fluorescence correlation spectroscopy, we further show that the precipitation is complete in 1 day, after which the size distribution of Abeta monomer/oligomers in the solution phase become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
130
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 40 publications
12
130
1
1
Order By: Relevance
“…The equilibrium monomer concentration observed in these experiments was substantially less than 100 nM, and lower than concentrations previously reported by several other laboratories (25)(26)(27). It is unlikely that small amounts of monomer are being lost in our system because a standard curve calibrated by amino acid analysis was linear down to 100 nM and had a zero intercept.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The equilibrium monomer concentration observed in these experiments was substantially less than 100 nM, and lower than concentrations previously reported by several other laboratories (25)(26)(27). It is unlikely that small amounts of monomer are being lost in our system because a standard curve calibrated by amino acid analysis was linear down to 100 nM and had a zero intercept.…”
Section: Discussioncontrasting
confidence: 55%
“…More importantly, however, the number of filaments in these fibrils changed frequently along the length of the fibril. Therefore, it is likely that the internal structure of the fibrils examined in this work differs from fibrils generated in other labs that exhibit lower thermodynamic stabilities (25)(26)(27), and those that yield narrow MPL distributions and narrow NMR spectra (7,28).…”
mentioning
confidence: 90%
“…There are two reasons for this simplification. First, the low protein concentrations found in vivo 19,20 will greatly favor monomeric pathways relative to the high concentration systems studied in vitro. 21 Second, the reduced complexity of monomeric growth makes the first-order process an obvious starting point.…”
Section: Introductionmentioning
confidence: 99%
“…By itself, resveratrol is a potent anti-oxidant which is thought to be responsible for the French Paradox [65]; relating to the low incidence of cardiovascular disease in a French population with high intake of saturated fats. In addition to its demonstrated capacity to inhibit (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) fibril formation in vitro [16], resveratrol is also capable of promoting intracellular uptake and degradation of through a proteosome-dependent mechanism [66] and protecting against -induced neurotoxicity [67,68], possibly through activation of the NAD-dependent histone deacetylase, SIRT1 [69]. In the present study using the ELISA-based assay, catechin showed no inhibitory activity during the early stages of oligomerization, whereas rosmarinic acid demonstrated some activity at the highest concentration tested.…”
Section: Discussionmentioning
confidence: 99%
“…Questions have arisen asking if these in vitro reactions are truly reflective of oligomerization in vivo since it is unlikely that localized brain levels of peptide would ever reach these concentrations [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%